Semiotika Poster Dakwah Instagram @hijrahfest: Perspektif Al-Qur’an dan Hadis - Erlina Yulianti; Sunaryanto (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2024)
This study analyzes the semiotic meaning of the da'wah posters on the Instagram account @hijrahfest based on Islamic values (specifically the prophetic hadith). The research method is qualitative with a mass media textual analysis. Data collection was done through documentation and observation of the Instagram account @hijrahfest. The data analysis method used is Ferdinand De Saussure's semiotics. The conclusion of this study shows, in terms of semiotics, the da'wah poster on the Instagram account @hijrahfest contains messages of sharia and morality based on the Qur'an and the Hadith of Prophet Muhammad SAW. The Qur'an invites believers to repent and return to Allah SWT, while the Hadith emphasizes the importance of hijrah both physically and spiritually. The da'wah message reminds Muslims to leave actions that contradict sharia, such as hurting parents and neglecting prayer. The connotation that arises shows that although there is a desire for salvation, behavior that does not align with Islamic teachings remains a challenge in the lives of Muslims.